Strategi Pemasaran Usaha Bakso AT Surabaya Republic Foodcourt di Manado Town Square - Nadeak, Roguintan; Mandei, Juliana Ruth; Rumagit, Grace Adonia Josefina (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
This research aims to identify marketing strategies carried out at the Bakso AT Surabaya Republic Foodcourt culinary business at Manado Town Square. The implementation of this research was carried out for 4 months, namely from March to June 2023. Primary data is obtained from direct interviews with consumers using a questionnaire. Secondary data is obtained through literature or references related to the research conducted. With a total of 44 respondents. The sampling technique used is accidental sampling. Based on the results of the research, the marketing strategy applied by Bakso AT Surabaya in the aspects of product (product), price (price), place (distribution), promotion (promotion), people (participants), process (process) and physical evidence (physical evidence) is classified as good.